Assessing Variations in Host Resistance to Fusarium oxysporum f sp. cubense Race 4 in Musa Species, With a Focus on the Subtropical Race 4 - Chen, Andrew; Sun, Jiaman; Matthews, Andrea; Armas-Egas, Liz; Chen, Ning; Hamill, Sharon; Mintoff, Sharl; Tran-Nguyen, Lucy T. T.; Batley, Jaqueline; Aitken, Elizabeth A. B. (Frontiers in Microbiology, 2019)
Fusarium oxysporum f. sp. cubense (Foc) has severely curtailed banana production in the tropical regions of the world. The tropical race 4 (TR4) of Foc was first detected in Australia in the late 1990s and it is virulent to all Cavendish type banana cultivars which represents the majority of banana production in Australia. Genetic resistance to Foc race 4 is urgently needed. To identify resistance, we have characterised the Foc resistance response of 34 Musa cultivars in glass and shade houses with plants grown under controlled settings. Amongst diploid banana cultivars carrying the AA genome, resistance is found in Musa acuminata sub-species including malaccensis (Pahang) and burmannica (Calcutta4). In the polyploid group, the hybrids such as FHIA-18 and FHIA-25 are highly resistant against both Foc-TR4 and subtropical race 4 (Foc-STR4). Interestingly, FHIA-2 and CAM020 appear to be resistant to Foc-TR4 but susceptible to Foc-STR4, suggesting potential differences in the resistance mechanisms against the different race 4 strains. Using a GFP tagged Foc-STR4 strain challenged onto Malaccensis lines of both resistant and susceptible types, a high inoculum dosage rapidly induced vascular wilt in the susceptible Malaccensis lines at 2.5 weeks. This was associated with an accumulation of micro-conidia in the rhizome and the movement of the fungus through the pseudostem. In contrast, the fungal movement was restrained in the rhizome of the resistant Malaccensis and no sporulation was observed. Overall, this research suggests that the resistance response is dependent to an extent on inoculum dosage and that the plant host’s response, in the rhizome, plays an important role in inhibiting the fungus from spreading to the rest of the plant. Identifying race 4 resistant accessions can help to understand mechanisms of resistance and provide banana breeders with the genetic resources to integrate resistance genes into commercial varieties.